2001
DOI: 10.1182/blood.v98.9.2837
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D3 is a target gene of t(6;14)(p21.1;q32.3) of mature B-cell malignancies

Abstract: Chromosomal translocation t(6;14)(p21.1; q32.3) has been reported as a rare but recurrent event not only in myeloma and plasma cell leukemia but also in diffuse large B-cell non-Hodgkin lymphoma (B-NHL) (diffuse large B-cell lymphoma [DLBCL]) and splenic lymphoma with villous lymphocytes (SLVL); however, the nature of the target gene(s) has not been determined. This study identified t(6; 14)(p21.1;q32.3) in 3 cases of transformed extranodal marginal zone B-NHL, in 1 case of SLVL, and in 1 case of a low-grade B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
104
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 46 publications
2
104
0
Order By: Relevance
“…8 None of the cases we analyzed by FISH showed the t(6;14) translocation, suggesting that this may be an extremely uncommon event in FL. Nevertheless, we found extrasignals of the cyclin D3 gene in 2 of 34 cases.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…8 None of the cases we analyzed by FISH showed the t(6;14) translocation, suggesting that this may be an extremely uncommon event in FL. Nevertheless, we found extrasignals of the cyclin D3 gene in 2 of 34 cases.…”
Section: Discussionmentioning
confidence: 86%
“…33 It has been suggested that, similarly to cyclin D1 in mantle cell lymphoma and plasma cell myeloma, cyclin D3 may be deregulated in hematopoietic disorders as a consequence of the t(6;14) translocation. 7,8 In particular, Shaughnessy et al 7 and Sonoki et al 8 found that cyclin D3 expression was associated with the t(6;14) translocation in approximately 5% of plasma cell myelomas and in sporadic cases of NHLs, respectively. In the above study, however, cyclin D3 IR has not been assayed in a matched series of cases lacking the t(6;14) translocation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Translocations that fuse CCND3 to IgH or other genes are observed in human B lineage lymphomas including Mantle Cell Lymphoma, Multiple Myeloma, and Diffuse Large B Cell Lymphoma. [30][31][32] These translocations have been proposed to drive cancer by accelerating proliferation through transcriptional upregulation of CYCLIN D3 protein. Considering that B lineage cancers with CCND3 translocations harbor additional genomic lesions arising from aberrant repair of DSBs, our data suggest that formation of CCND3 translocations in immature B cells may lead to mature B cell malignancies by disrupting regulation of G1-to-S progression in developing B cells.…”
Section: Discussionmentioning
confidence: 99%